Evolution of performance imagery among elite team-sport professionals from former communist Romania. - Diaconescu, Andy. (University of Ottawa (Canada), 1993)
In-depth interviews were conducted with eight European life-long sport professionals who were former elite athletes and then successful coaches in team sports. The purpose of the interview was to explore the role and the evolution of imagery from athlete to coach and to also determine whether mental imagery was used in any way by these professional coaches for enhancing team unity. Analysis showed that all these exceptional performers had excellent imagery skills and they used imagery training to achieve their sport related goals. Practical implications for enhancing team unity through imagery are also presented.
Keywords: Anthropology, Cultural.